2001
DOI: 10.1021/jp0034729
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Investigation of the Heterogeneous Reaction of HNO3 and NaCl(100)

Abstract: We have monitored the reaction of HNO3 with the NaCl(100) faces of single crystals in the presence of minute water concentrations. The reaction produces NaNO3 crystallites or ribbons atop the NaCl(100) face, indicating that a surface reorganization occurs upon exposure to water vapor concentrations as low as 0.02 mbar. The crystalline nature of the NaNO3 is established by the well-defined longitudinal-transverse (LO-TO) splitting of the NO3 - stretching vibrations. After an average coverage of 10 to 30 layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 32 publications
8
26
0
Order By: Relevance
“…A sample of condensed-phase nitric acid was prepared by applying a droplet of nitric acid to the Teflon filter. The observed vibration peaks between 860 and 900 cm −1 of nitric acid ( Figure 1b) were consistent with reported peak assignments (McGraw et al 1965;Maki and Wells 1992;Sporleder and Ewing 2001). These peaks differ significantly from the 849 cm −1 peak of ON groups and were not observed in SOA samples, suggesting that nitric acid, a terminal sink of NO x , was either not present in the particle phase or below DL of the FTIR analysis (the DL of HNO 3 is not quantified, but is estimated at 0.01 µg m −3 based on the DL of ON groups).…”
Section: Identification and Quantification Of On Groupssupporting
confidence: 90%
“…A sample of condensed-phase nitric acid was prepared by applying a droplet of nitric acid to the Teflon filter. The observed vibration peaks between 860 and 900 cm −1 of nitric acid ( Figure 1b) were consistent with reported peak assignments (McGraw et al 1965;Maki and Wells 1992;Sporleder and Ewing 2001). These peaks differ significantly from the 849 cm −1 peak of ON groups and were not observed in SOA samples, suggesting that nitric acid, a terminal sink of NO x , was either not present in the particle phase or below DL of the FTIR analysis (the DL of HNO 3 is not quantified, but is estimated at 0.01 µg m −3 based on the DL of ON groups).…”
Section: Identification and Quantification Of On Groupssupporting
confidence: 90%
“…83 Additional bands due to O-H stretches of HNO 3 Á(H 2 O) n (n = 1-3) complexes were also observed in the present study between 2400 and 3200 cm À1 (not shown), similar to what was observed previously. 22 The presence of nitrate and nitric acid-water complexes suggests that residual water remains on the surface of the IRE, despite efforts to remove it under vacuum.…”
Section: Atr-ftir Investigation Of Hno 3 -No X Surface Filmssupporting
confidence: 92%
“…Longitudinal-transverse ͑LO-TO͒ splitting was reported by Fox and Hexter, 23 according to which the crystal shape can lower the overall environmental symmetry and lift the degeneracies of infrared models. When a NaNO 3 crystal appears as a thin plate, a single feature from the bulk crystal may be split, 24 as observed by Devlin et al for a thin crystalline plate of NaNO 3 on substrate. 25 In this work, the solid samples were obtained by drying the NaNO 3 droplets on the ZnSe substrate, and therefore thin plates may form and give rise to the splitting of the 3 -NO 3 − band.…”
Section: Ftir-atr Spectra Features and Phase Transitions Of Nano 3 Pamentioning
confidence: 72%